Multiparameter acceleration characteristics of premixed methane/air explosion in a semi-confined pipe. (September 2017) - Jiang, Bingyou; Tang, Mingyun; Shi, Shulei
Abstract: After a semi-confined pipe with a cross-section area of 0.08 × 0.08 m 2 and a length of 21 m, the multiparameter acceleration characteristics of a methane/air mixture with a fuel concentration of 9.5% and a filling ratio of 100% were simulated. The results show that a shock wave and a sonic compression wave produce two peak overpressures after 4.16 m away from the ignition source. The maximum overpressure presents a changing trend of decreasing and increasing with increasing distance. With increasing distance from the ignition source, the peak overpressure formed by shock wave, the flame propagation speed, the maximum combustion rate, the maximum density, and the maximum gas velocity increased gradually, but the peak overpressure formed by sonic compression wave and the maximum temperature decreased gradually. This will provide a basis of gas explosion control research. Highlights: Multiparameter acceleration characteristics of a gas explosion were revealed. Peak overpressure formed by shock wave increased with increasing distance. Peak overpressure formed by sonic compression wave decreased with distance. Maximum overpressure decreased initially and then increased with distance. Maximum combustion rate, density and gas velocity increased with distance.